"The Next Level": Investigating teaching and learning within an Irish traditional music online community. (December 2013) - Kenny, Ailbhe
Online music communities offer a new context and culture for musical participation globally. This article, employing a socio-cultural theoretical lens, examines how the Online Academy of Irish Music (OAIM) functions as a teaching and learning online community for Irish traditional music. Findings from qualitative case study research present observations of practice from the OAIM website, forums, video tutorials, and Facebook posts over a 9-month period. In addition to these collective insights, findings from participant logs and interviews with the tutors offer individual insights into the online case study. Questions are posed regarding the pedagogy of e-learning, the development of a "shared practice" and the influence of roles and relationships within the community. The online medium of interaction raises important issues for the growing technological culture of music teaching and learning and the study seeks to understand this new context for musical participation.